Aryl Hydrocarbon Receptor Deficiency in an Exon 3 Deletion Mouse Model Promotes Hematopoietic Stem Cell Proliferation and Impacts Endosteal Niche Cells - Zeenath Unnisa; Kameshwar P. Singh; Ellen C. Henry; Catherine L. Donegan; John A. Bennett; Thomas A. Gasiewicz (Stem Cells International)
The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor belonging to the Per-Arnt-Sim (PAS) family of proteins. The AHR is involved in hematopoietic stem cell (HSC) functions including self-renewal, proliferation, quiescence, and differentiation. We hypothesize that AHR impacts HSC functions by influencing genes that have roles in HSC maintenance and function and that this may occur through regulation of bone marrow (BM) niche cells. We examined BM and niche cells harvested from 8-week-old AHR null-allele (KO) mice in which exon 3 was deleted in the Ahr gene and compared these data to cells from B6 control mice; young and old (10 months) animals were also compared. We report changes in HSCs and peripheral blood cells in mice lacking AHR. Serial transplantation assays revealed a significant increase in long term HSCs. There was a significant increase in mesenchymal stem cells constituting the endosteal BM niche. Gene expression analyses of HSCs revealed an increase in expression of genes involved in proliferation and maintenance of quiescence. Our studies infer that loss of AHR results in increased proliferation and self-renewal of long term HSCs, in part, by influencing the microenvironment in the niche regulating the balance between quiescence and proliferation in HSCs.